Pelatihan Pengelasan SMAW Karang Taruna Desa Kresik Putih, Kecamatan Batulicin, Kabupaten Tanah Bumbu - Jefri Aldo Aldo; Sandi Kurniawan; Rifki Asrul Sani; Rexanda Saveta; Hariyono Hariyono (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Welding technology is an applied technology, where this technology can be applied or applied in the form of products, both small and large products. The application of welding technology can be carried out in the world of education and society, in the world of education it can be done with formal education carried out in schools while in the community it can be done using training. Welding training in the community is carried out with a community service program, namely the SMAW welding training service in the village of Kresik Putih, this training applies SMAW welding technology to become a product. The training starts with an explanation of K3, an explanation of tools and materials, an explanation of the welding position, and welding applications to make products. The resulting product is a flower fitting holder used for the white creek village office. This training has had a positive impact on the community, where previously the community had not been able to understand welding technology, especially SMAW. This training can be used as capital to develop entrepreneurship.